Analysing architecture - Unwin, Simon, 1952- (Routledge, 2014)
"Now in its fourth edition, Analysing Architecture has become internationally established as the best introduction to architecture. Aimed primarily at those wishing to become professional architects, it also offers those in disciplines related to architecture (from archaeology to stage design, garden design to installation art), a clear and accessible insight into the workings of this rich and fascinating subject. With copious illustrations from his own notebooks, the author dissects examples from around the world and all periods of history to explain underlying strategies in architectural design and show how drawing may be used as a medium for analysis"--